The Effectiveness of Using Maudy Ayunda as a Brand Ambassador of Oatside Milk for Indonesian People - Rachel Joeyceline Kai; Agusly Irawan Aritonang; Lady Joanne Tjahyana (Journal of Content and Engagement, 2024)
This research measures the effectiveness of using Maudy Ayunda as a brand ambassador in the marketing public relations (MPR) strategy for the Oatside milk product in Indonesian people. Maudy Ayunda, as a public figure with a positive reputation and wide influence, has been chosen to increase brand awareness and strengthen the positive image of the Oatside milk product. This research uses a survey method by collecting data through questionnaires distributed to 400 people in Indonesia using a Likert scale. The results of this research indicate that the use of Maudy Ayunda as a brand ambassador is effective based on the VisCAP indicators. VisCAP itself consists of visibility, credibility, attraction, and power. This research provides important insights for marketing practitioners in designing MPR strategies that leverage the strength of a brand ambassador to achieve desired communication and marketing goals. According to the research results, the attraction indicator has the most significant effectiveness among the three other indicators.